Emerging technologies for sustainable irrigation: Selected papers from the 2015 ASABE and IA irrigation symposium - Lamm, Freddie R.; Stone, K. C.; Dukes, M. D.; Howell, T. A., Sr.; Robbins, J. W. D., Jr.; Mecham, B. Q. (My University, 2016)
This article is an introduction to the "Emerging Technologies in Sustainable Irrigation: A Tribute to the Career of Terry Howell, Sr." Special Collection in this issue of Transactions of the ASABE and the next issue of Applied Engineering in Agriculture, consisting of 16 articles selected from 62 papers and presentations at the joint irrigation symposium of ASABE and the Irrigation Association (IA), which was held in November 2015 in Long Beach, California. The joint cooperation on irrigation symposia between ASABE and IA can be traced back to 1970, and this time period roughly coincides with the career of Dr. Howell. The cooperative symposia have offered an important venue for discussion of emerging technologies that can lead to sustainable irrigation. This most recent symposium is another point on the continuum. The articles in this Special Collection address three major topic areas: evapotranspiration measurement and determination, irrigation systems and their associated technologies, and irrigation scheduling and water management. While these 16 articles are not inclusive of all the important advances in irrigation since 1970, they illustrate that continued progress occurs by combining a recognition of the current status with the postulation of new ideas to advance our understanding of irrigation engineering and science. The global food and water challenges will require continued progress from our portion of the scientific community. This article serves to introduce and provide a brief summary of the Special Collection. © 2016 American Society of Agricultural and Biological Engineers.
Citation: Lamm, F. R., Stone, K. C., Dukes, M. D., Howell, T. A., Sr., Robbins, J. W. D., Jr., & Mecham, B. Q. (2016). Emerging technologies for sustainable irrigation: Selected papers from the 2015 ASABE and IA irrigation symposium. Transactions of the Asabe, 59(1), 155-161. doi:10.13031/trans.59.11706
Keywords: Center-Pivot Sprinkler Irrigation; Deficit Irrigation; Evapotranspiration; Irrigation Management; Irrigation Scheduling; Microirrigation